Laparoscopic ureteral reimplantation: prospective evaluation of medium-term results and current developments - Gözen, Ali Serdar; Cresswell, Joanne; Canda, Abdullah Erdem; Ganta, Suresh; Rassweiler, Jens; Teber, Dogu (World journal of urology, 2010)
Laparoscopic ureteral reimplantation is a feasible method for treating ureteral pathology with good preliminary results in the literature. In this study, we review our medium-term results for laparoscopic ureteral reimplantation and discuss current developments of this procedure.